Potencial biotecnológico de leveduras fermentadoras de D-xilose isoladas de regiões de Floresta Amazônica Brasileira - Raquel Miranda Cadete (2013)
Environmental, economical, political, geographical and social purposes have recently driven the search for the production of sustainable fuels. In this scenario, second generation (2G) ethanol is considered the main renewable fuel, and an efficient conversion of sugars from lignocellulosic materials into ethanol has become a world priority for an environmentally friendly production of this energy source, at feasible costs. The aims of this study were to isolate, identify and characterize yeasts able to ferment D-xylose, the second main monosaccharide in plant biomass, regarding to the employment of these microorganisms in the production of 2G ethanol. A total of 224 yeast strains were isolated from 40 rotting wood samples collected in areas of Brazilian Amazonian Forest. Of the 33 species identified, 26 were previously known and seven were new. Within these new species, five were ascribed to the main xylose-fermenting clades, Scheffersomyces clade, represented by Sc. amazonensis; and Spathaspora clade, represented by Sp. brasiliensis, Sp. roraimanensis, Sp. suhii e Sp. xylofermentans. Besides these new species, six strains of Sp. passalidarum were also found. From D-xylose fermentation assays performed with complex medium and sugarcane bagasse hydrolysate, and the determination of enzymatic activities and co-factors usage of xylose reductase (XR) and xylitol dehydrogenase (XDH), it was possible to characterize the studied yeasts according to achievement of ethanol or xylitol as main metabolic product. Xylitol- producing species (Sc. amazonensis, Sp. brasiliensis, Sp. roraimanensis, Sp. suhii and Sp. xylofermentans) showed XR activities absolutely dependent of NADPH. Spathaspora arborariae and Sp. passalidarum, ethanol-producing species, presented XR activity using both NADH and NADPH as cofactors, and in Sp. passalidarum this is accomplished by a XR with preference for NADH. The identification of XR encoding genes (XYL1) in the evaluated Spathaspora species revealed that Sp. passalidarum is the sole harboring two XYL1 genes, XYL1.1 and XYL1.2. In the remaining species, a unique gene, XYL1, was found, encoding a XR (XYL1.p) showing a higher homology to the XR encoded by XYL1.1 (XYL1.1p) than by XYL1.2 (XYL1.2p). XYL1.2p is a NADH-preferred XR, feature able to sustain a co-factor balance in the first steps of the D-xylose metabolism, giving the yeast a remarkably ability to produce ethanol during this process. This enzyme exclusively has an aspartic acid residue in the position 271 of the co-factor binding site instead of an asparagin residue, the latter found in the corresponding position in the majority of the remaining analyzed XRs. This feature is directly related to the preference for NADH showed by XYL1.2p. Heterologous expression of XYL1.1 and XYL1.2 from Sp. passalidarum type strain and a Brazilian strain allowed the investigation of each gene behavior during the metabolism of D-xylose in S. cerevisiae. The transformant generated with XYL1.2 from the Brazilian strain displayed a fast and high conversion of D-xylose to ethanol under anaerobic conditions together with a low production of xylitol. The results of this work contributes to demonstrate the potential of studying new D-xylose-fermenting yeast species and strains isolated in Brazilian biomes with regard to evolutionary, taxonomic and biotechnological applications of these micro-organisms. The construction of a S. cerevisiae strain with an unprecedented gene and capable of fermenting D-xylose under anaerobic conditions, displaying high ethanol yield and productivity, stands as a relevant contribution in the improvement of second generation ethanol production through efficient D-xylose fermentation.